Streamline Effect Improvement of Additive Manufactured Airfoil Utilizing Dynamic Stream Control Procedure. (17th September 2022) - Srinath, R.; Mukesh, R.; Poojari, Manish C.; Hasan, Inamul; Amare Alebachew, Wubetu
Abstract : In the era of fast transport, to create inventive stream flow management solutions that are capable of diminishing the aerodynamic drag of the vehicles, there is a need to modify the flow characteristics over the vehicle by deferring or expelling the position of the flow partition. The objective of this study involves the parameterized design of an airfoil utilizing the Bezier curve technique with the assistance of the simulation program. For flow regulations, synthetic jet modules are ingrained at different percentages of the chord to manage the stall characteristics. The parametrization system, combined with the stream control method, can give a much better insight into flow re-energization and pave some way for the reduction of the wake. Digital fabrication technique (3d printing or Rapid Prototyping method) is used to fabricate the end product for aerodynamic testing. The comparative outcome showed a reduction in drag at certain angles of attack due to the surface finish obtained. By comparing the results, the aerodynamic efficiency showed a significant rise of 13.05% at lower angles of attack when compressed gas was used in the synthetic jet closer to the frontier edge of the airfoil. Near the stall angle of attack, the coefficient of lift ( Cl ) and coefficient of drag ( Cd ) values showed no progress.